Pathways of phosphorous fraction dynamics in field crop rotations of the pampas of Argentina - Ciampitti, Ignacio A. (2011)
The study of labile and nonlabile forms of P might contribute to advances in soil test procedures and provide insights into management strategies to enhance P bioavailability to crops. Our objective was to evaluate the effect of continuous P fertilization on inorganic (Pi) and organic (Po) P fractions to improve the understanding of soil P dynamics. For this purpose, four on-farm experiments were analyzed during a 6-yr period. Two sites followed the corn (Zea mays L.)-double cropped wheat (Triticum aestivum L.)/soybean [Glycine max (L.) Merr.] rotation and two sites followed the corn-soybean-double cropped wheat/soybean rotation. Phosphorus fertilization levels were 0 (Wp treatment) and 34 kg yr -1 (Fp treatment). The following soil P fractions were analyzed: anion exchange membrane (AEM) Pi, NaHCO 3-Pi and -Po, NaOH-Pi and -Po, HCl-Pi, and residual P. Path analysis of relationships among all P forms revealed that the main P fertilizer sinks were NaOH-Po and HCl-Pi fractions, accounting for approximately 50% of total applied P. The pathways for the Wp treatment showed the importance of Pi pools for the replenishment of available P, represented by the AEM-Pi and NaHCO 3-Pi fractions, and the role of NaOH-Pi along with HCl-Pi as major Pi sources. When P fertilizer addition exceeded plant P removal, the pathway analysis showed that the Pi fractions tended to reorganize into more stable Po fractions. Path analysis was a practical tool to elucidate the roles of different Po and Pi pools in the transformations induced by differences in nutrient input and crop removal. © Soil Science Society of America.